Adaptarse para resistir - Ana A. Teruel (Caravelle)
This text analyzes the measures and the judicial and extrajudicial procedings used by peasants from the highlands (uplands) in the province of Jujuy, Argentina, to defend and claim property rights concerned with disentailment, since 1830. In a period of time that reaches up to the 1920’s, it  exposes how questions inherent to those rights were settled by the governors and courts in the administrative sphere. Simultaneously, explaining the changes and farmers’ claims on the property.